Playful simulations rather than serious games: medical simulation as a cultural practice - Pelletier,C; Kneebone,R (Games and Culture, 2015)
Medical simulation has historically been studied in terms of the delivery of learning outcomes or the social construction of knowledge. Consequently, simulation-based medical education has been researched primarily in terms of the transfer of skills or the reproduction of professional communities of practice. We make a case for studying simulation-based medical education as a cultural practice, situating it within a history of gaming and simulation, and which, by virtue of distinctive aesthetics, does not simply teach skills or reproduce professional practices but rather transforms how medicine can be made sense of. Three concepts from the field of game studies—play, narrative, and simulation—are deployed to interpret an ethnographic study of hospital-based simulation centers and describe underreported phenomena, including the cooperative work involved in maintaining a fictional world, the narrative conventions by which medical intervention are portrayed, and the political consequences of simulating the division of labor.